Energy cost of seed drying - Weerachet Jittanit; George Srzednicki; Robert Driscoll (Universitas Gadjah Mada, 2009)
In this work, the energy costs of drying corn, rice and wheat seeds between 3 drying options were compared. They consisted of 1) two-stage drying by using fluidised bed dryer (FBD) in the 1st stage and in-store dryer (ISD) in the 2nd stage, 2) single-stage drying by fixed bed dryer (FXD) and 3) two-stage drying by using FXD in the 1st stage and ISD in the 2nd stage. The drying conditions selected for comparison were proved to be safe for seed viability by the previous studies. The results showed that the drying options 2 and 3 consumed less energy than option 1. However, the benefits from lower energy cost must be weighed against some advantages of using FBD. Furthermore, it appeared that running the burners of FXD and ISD for warming up the ambient air during humid weather condition could shorten drying time significantly with a little higher energy cost.